The French in Indo-China : with a narrative of Garnier's explorations in CochinChina, Annam and Tonkin - Meyers, Dean (Bangkok, Thailand : White Lotus, 1994)
Narrative based on authors and other two French explorers, Henri Mouhot, 1826-1861 and Dr. Morice, fl. 1850-1880 travel accounts to Indochina between 1860-1875
Originally published by T. Nelson and Sons, Patternoster Row, Edinburgh, 1884-- title page
Keywords: Garnier, Francis, -- 1839-1873 -- Travel -- Indochina; Mouhot, Henri, -- 1826-1861 -- Travel -- Indochina; Morice, -- fl. 1850-1880 -- Travel -- Indochina; Indochina -- Description and travel; Mekong River -- Discovery and exploration -- French